The Concept of Peace in Conflict (Analysis of Western and Islamic Political Thought Theory): Konsep Perdamaian Dalam Konflik (Analisis Teori Pemikiran Politik Barat dan Islam) - Damanik, Karmila; Junaidi, Junaidi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Western political thought is often based on principles such as democracy, human rights and secular systems. The concept of peace in Western political thought is often related to diplomacy, conflict resolution through negotiation, as well as the recognition of human rights as a universal foundation for peace. This research examines the concept of peace in conflict from the perspective of Western and Islamic political thought. Aristotle focused on the concept of justice and good forms of government, including monarchy, aristocracy and democracy. Al-Farabi: Developed the concept of an ideal state oriented towards morality and ethics. He believed that politics should lead to the happiness of society. Western political thought emphasizes diplomacy, democracy, human rights, free trade and tolerance as the foundations of peace. Meanwhile, Islamic political thought prioritizes upholding justice, sharia law, and security as the foundation of peace, and introduces the concept of jihad as an effort to defend justice. This study uses a qualitative research method with a literature study approach, analyzing literature sources related to Western and Islamic political thought. The results of the analysis show that despite their principled differences, the two traditions share values such as tolerance and interfaith dialogue that can contribute to global conflict resolution. By understanding the potential common ground, this research offers a more inclusive and holistic approach in addressing the complex conflicts of the modern world.